Effect of Coconut Water on Dysmenorrhea Among Adolescent at Senior High School 104 East Jakarta - Dahlan, Febry Mutiariami; Choirunissa, Risza; Setya, Erien Wahyu (Rajaki of Tulip Medika Publisher, 2023)
According to WHO (2012), an incidence of 1,769,425 people (90%) was found in women with dysmenorrhea with 10-15% experiencing severe dysmenorrhea. Based on data from the National Health and Nutrition Examination Survey (NHANES), the average age of menarche in adolescents in Indonesia is 12.5 years with a range of 9-14. In Indonesia the incidence of primary dysmenorrhea is around 54.89% while the remaining sufferers with secondary dysmenorrhea. To examine the effect of coconut water on dysmenorrhea among students at the Senior High School 104 East Jakarta. This was a quasy-experimental design by using pre-test and post-test with control group. There were 30 participants in the experiment group and 15 others in the control group. The NRS was conducted as an instrument, the data analyzed by using Wilcoxon sign rank and Mann Whitney. The results showed thatthe pretest and posttest frequency distribution data of the experimental group found 4 people (26.7%) mild pain, 8 people (53.3%) moderate pain and 3 people (20.0%) severe pain. Whereas after the posttest treatment decreased, there were no pain 4 respondents (26.7%), mild pain 8 respondents (53.3%), moderate pain 2 people (13.3) and severe pain as much as 1 person (6, 7%). That there is an influence of coconut water on menstrual pain with a p value of 0.019 (p <0.05), therefore Ho is rejected and Ha is accepted. Coconut affects the decrease in dismenorhe pain. It is recommended to young women to apply drinking young coconut water to reduce dismenorhe pain.